The Effect of Using Oral History as An Approach on The Achievement of Sixth Grade Students in The National Education Subject and in Development Their National Values in Jordan - Al- Mehsen, Nassra Hani; Abu Sneineh, Odeh Abduljawwad (Journal of Educational and Psychological Sciences, 2019)
The aim of this study was to measure the effect of the use of oral history on the achievement of the sixth grade students in national education and the development of their national values. The study sample consisted of (60) students of the sixth grade in the Directorate of Education in the Direla District، The second method was used for the academic year 2017/2018. The semi- experimental method was used by randomly dividing the study sample into two experimental and control groups. In order to achieve the objectives of the study، the mean and standard deviations were used، and ANCOVA was analyzed.
Keywords: education; oral history; national education; sixth grade; national values